2018
DOI: 10.1097/yic.0000000000000193
|View full text |Cite
|
Sign up to set email alerts
|

Implications of infection and trends of antibiotic prescribing in hospitalized patients diagnosed with serious mental illness

Abstract: Hospital-acquired infections have been recognized as a significant factor in increased morbidity and mortality across our health system. Unique to infections associated with inpatient psychiatric hospitalization is the additional hypothesized association of the role that antipsychotic agents and/or underlying disease may play in an increased risk for infection. In this paper, we explore the types of infections diagnosed in an inpatient psychiatric hospital, the demographics of the patients infected, and whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Furthermore, patients with psychiatric illnesses are at 9 times higher risk of developing urinary tract infections than the general population. 4 In a psychiatric clinic in Switzerland, the surfaces of TMS magnetic coils were investigated before (n = 25) and after (n = 25) disinfection the morning before any treatment. To measure the impact that the patients had on the surface, probes were taken after treatment without any disinfection (n = 25) and 25 times with disinfection after every patient to show the effect of regularly performed disinfection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, patients with psychiatric illnesses are at 9 times higher risk of developing urinary tract infections than the general population. 4 In a psychiatric clinic in Switzerland, the surfaces of TMS magnetic coils were investigated before (n = 25) and after (n = 25) disinfection the morning before any treatment. To measure the impact that the patients had on the surface, probes were taken after treatment without any disinfection (n = 25) and 25 times with disinfection after every patient to show the effect of regularly performed disinfection.…”
mentioning
confidence: 99%
“…It was found that they can worsen psychosis. Furthermore, patients with psychiatric illnesses are at 9 times higher risk of developing urinary tract infections than the general population 4 …”
mentioning
confidence: 99%